Application of gas chromatography–mass spectrometry (GC‐MS)‐based metabolomics for the study of fermented cereal and legume foods: A review. (28th September 2020) - Adebo, Oluwafemi Ayodeji; Oyeyinka, Samson Adeoye; Adebiyi, Janet Adeyinka; Feng, Xi; Wilkin, Jonathan D.; Kewuyemi, Yusuf Olamide; Abrahams, Adrian Mark; Tugizimana, Fidele
Abstract: A new era of cutting‐edge technologies and advancements in analytical platforms and omics sciences is disruptively bringing a paradigm shift in fundamental and translational research. Metabolomics is one of the omics strategies that yields big data and has gained popularity in a wide spectrum of applications. Among various analytical platforms used in metabolomics, gas chromatography–mass spectrometry (GC‐MS) allows the measurement of thermally stable (volatiles and semi‐volatiles) metabolites, with an advantage of spectral reproducibility. Cereal‐ and legume‐based fermented foods are part of the food culture in various countries throughout the world. Thus, this review provides an overview of recent applications of GC‐MS‐based metabolomics in the food fermentation field, specifically cereal‐ and legume‐based fermented foods. This emerging use of metabolomics in food fermentation studies illustrates the potentials of this omics science to elucidate metabolome landscapes of fermented foods. Such insights would advance our predictive understanding of fermentation processes and molecular descriptions of resultant food products, a necessary step for improvements and sustainability in food industry. Furthermore, the review echoes the current need of collaborative efforts in the scientific community (in this field) to harness and maximise the potentials of metabolomics in food fermentation studies. Abstract : GC‐MS‐based metabolomics for fermented cereal and legume foods